2020
DOI: 10.1101/2020.04.13.038752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioinformatic characterization of angiotensin-converting enzyme 2, the entry receptor for SARS-CoV-2

Abstract: The World Health Organization declared the COVID-19 epidemic a public health emergency of international concern on March 11th, 2020, and the pandemic is rapidly spreading worldwide.COVID-19 is caused by a novel coronavirus SARS-CoV-2, which enters human target cells via angiotensin converting enzyme 2 (ACE2). We used a number of bioinformatics tools to computationally characterize ACE2 by determining its cell-specific expression, putative functions, and transcriptional regulation. The small intestine expressed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 81 publications
0
11
0
8
Order By: Relevance
“…However, clinicians still should assess the reproductive function of male COVID-19 patients for prognosis. It was also found that the expression of ACE2 in adipose tissue was relatively high, which indicated that infection of SARS-CoV-2 may be related with obesity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinicians still should assess the reproductive function of male COVID-19 patients for prognosis. It was also found that the expression of ACE2 in adipose tissue was relatively high, which indicated that infection of SARS-CoV-2 may be related with obesity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expressions of ACE2 in different human organs were analyzed and the results showed that ACE2 was expressed in the heart [ 27 , 34 ]. Furthermore, Chen et al analyzed the feature of ACE2 expressions among cardiac cell types and found that ACE2 was specifically expressed in pericyte [ 35 ].…”
Section: The Mrna Expressions Of Ace2 and Tmprss2 In Extrapulmonary Omentioning
confidence: 99%
“…We have found that ACE2 mRNA expression is mainly found in gastrointestinal (GI) tract and the small intestine has the highest level of ACE2 levels compared to other organs in this study. Diarrhea is one of major symptoms of COVID-19 and high numbers of ACE2 positive small intestine cells occur in COVID-19 patients [43]. This indicates that SARS-CoV-2 also may also affect the GI tract through the ACE2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 expression in the gastrointestinal tract is primarily found in absorptive enterocytes, 7,37 which could indirectly be confirmed through the significant correlation (p<2.2E-16) between mucosal ACE2 and several epithelial marker genes (APOA1, SI, FABP6, ENPEP) (Supplementary Figure S2). To further examine the expression of genes associated with risk of SARS-CoV-2 infection in IBD patients, we employed sc-RNA seq to profile transmural biopsies of (un)inflamed regions of resected tissue from six CD patients undergoing ileocaecal resection.…”
Section: Decrease Of Ace2/tmprss2 Double Positive Cells In Inflamed Ileum But Not In Colonmentioning
confidence: 80%